Status of the leatherback turtle, dermochelys coriacea - Chan, E. H. (1987)
This paper reviews the status of biological knowledge on the leatherback turtle, provides estimates on the major nesting population of the world and in South-East Asia, assesses its nesting status in Terengganu, Malaysia and discusses conservation and research needs.